Опыт разработки автоматизированных систем для поведения гистологических исследований - Аврунин, О. Г.; Масловский, C. Ю.; Носова, Т. В.; Масловский, А. С.; Семенец, В. В. (ХНУРЭ, 2008)
The work is devoted to design the system for automatical histological research. The problems of digital processing for histological images are described. The root principles of design, main issues of imaging' processing and structure of the system for automatical histological research are proposed. Main medical-technical requirements for proposed system are considered.
Keywords: гистология; биомединженерия